2012
DOI: 10.5897/ajpp11.186
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Qing-Shu-Yi-Qi-Tang reduce lung cancer-induced cachexia in mice

Abstract: This study is to investigate anti-inflammatory and anti-cachectic effect of Qing-Shu-Yi-Qi-Tang (QSYQT) in RAW 264.7 cells and Lewis lung cancer cells bearing mice. We examined the effect of QSYQT on LPS-induced inflammatory activity in a murine macrophage cell line, Raw 264.7. We evaluated cachectic parameters, such as weight loss, food intake and tumor size in tumor-bearing and non-tumor-bearing mice treated with QSYQT decoction or a normal diet. Cytokine production in cell culture and in cachectic mice was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It was found that Qingshu Yiqi decoction could prevent weight loss in mice without increasing food intake. Additionally, it could reduce the secretion of IL-1 β , IL-6, and TNF- α by mouse macrophages, thus producing an antitumor effect ( Chou et al, 2012 ). This study illustrates the antitumor effect of several compounds of Baizhu and provides a comprehensive basis for the antitumor effect of Baizhu.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…It was found that Qingshu Yiqi decoction could prevent weight loss in mice without increasing food intake. Additionally, it could reduce the secretion of IL-1 β , IL-6, and TNF- α by mouse macrophages, thus producing an antitumor effect ( Chou et al, 2012 ). This study illustrates the antitumor effect of several compounds of Baizhu and provides a comprehensive basis for the antitumor effect of Baizhu.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Of the 25 articles, 12 were excluded because they did not report in vivo research and/or were duplicates. As a result, we selected 13 in vivo studies for this study (Iizuka et al, 2000(Iizuka et al, , 2002Xu et al, 2005;Beckett et al, 2008;Fujitsuka et al, 2011;Chou et al, 2012;Wang et al, 2012;Yae et al, 2012;Choi et al, 2014;Terawaki et al, 2014;Ohbuchi et al, 2015;Kim et al, 2016;Zhuang et al, 2016) (Fig. 1).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…QSYQT, composed of Astragalus membranaceus Bunge, Panax ginseng C. A. Meyer, Atractylodes chinensis Koidzumi, Cimicifuga foetida Linné, Atractylodes macrocephala Koidzumi, Alisma orientale Juzepzuk, Citrus reticulata Blanco, and Massa Medicata Fermentata, has been used for treating fever and pulmonary disorders in East Asia (Chou et al, 2012). A. membranaceus, A. chinensis, and P. ginseng, the major ingredients of QSYQT, have been investigated for their immunomodulatory and antiinflammatory activity Leung, 2007a, 2007b;Li et al, 2007;Dong et al, 2008;Agyemang et al, 2013;Fu et al, 2014;Li et al, 2014;Ru et al, 2015).…”
Section: Qing-shu-yi-qi-tang and S Baicalensismentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that Qingshu Yiqi decoction could prevent weight loss in mice without increasing food intake. Additionally, it could reduce the secretion of IL-1β, IL-6, and TNF-α by mouse macrophages, thus producing an antitumor effect (Chou et al, 2012). This study illustrates the antitumor effect of several compounds of Baizhu and provides a comprehensive basis for the antitumor effect of Baizhu.…”
Section: Antitumor Effect Of Prescriptionmentioning
confidence: 62%